2017
DOI: 10.1038/npp.2017.280
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Combinations of Alcohol, Nicotine, and Cannabis on Dynamic Brain Connectivity

Abstract: Alcohol, nicotine, and cannabis are among the most commonly used drugs. A prolonged and combined use of these substances can alter normal brain wiring in different ways depending on the consumed cocktail mixture. Brain connectivity alterations and their change with time can be assessed using functional magnetic resonance imaging (fMRI) because of its spatial and temporal content. Here, we estimated dynamic functional network connectivity (dFNC) as derived from fMRI data to investigate the effects of single or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 73 publications
3
39
0
Order By: Relevance
“…Alcohol-dose effects on brain activation were explored using ICA to isolate systematically nonoverlapping networks and their time courses (Calhoun, Pekar, & Pearlson, 2004). ICA and DFC analyses have been recently used to study alcohol, nicotine, and marijuana dependence (Vergara, Weiland, Hutchison, & Calhoun, 2018).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Alcohol-dose effects on brain activation were explored using ICA to isolate systematically nonoverlapping networks and their time courses (Calhoun, Pekar, & Pearlson, 2004). ICA and DFC analyses have been recently used to study alcohol, nicotine, and marijuana dependence (Vergara, Weiland, Hutchison, & Calhoun, 2018).…”
Section: Significancementioning
confidence: 99%
“…Alcohol‐dose effects on brain activation were explored using ICA to isolate systematically nonoverlapping networks and their time courses (Calhoun, Pekar, & Pearlson, ). ICA and DFC analyses have been recently used to study alcohol, nicotine, and marijuana dependence (Vergara, Weiland, Hutchison, & Calhoun, ). Networks found with ICA have been further used to study DFC characteristics in schizophrenia patients both with task (auditory oddball task) (Sakoglu & Calhoun, ; Sakoglu et al, ) and at rest (Sakoğlu & Calhoun, ; Sakoğlu, Michael, & Calhoun, ).…”
Section: Introductionmentioning
confidence: 99%
“…A widely utilized approach of looking at the brain’s resting state networks (RSNs) provides baseline information on the brain’s functional network architecture based on the temporal correlations of spatially distributed brain regions in the absence of a task (Biswal et al 1997). Existing studies in primarily cannabis and nicotine users indicate opposing effects of each substance (Subramaniam et al 2016), including in RSNs (Vergara et al 2018). For example, increased connectivity has been reported in cannabis users (Pujol et al 2014; Filbey et al 2014), whereas reduced connectivity has been observed in nicotine users (Weiland et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of artifacts in the form of spurious fluctuations was the main concern in this static case. Brain areas and dynamic states were extracted from previous work (Vergara et al, 2018). Although there is no ground truth, we can estimate quasi-static, quasi-sharp transitions and fluctuating dFNC using the dynamic state membership functions of each case.…”
Section: Real Data Examplementioning
confidence: 99%
“…Displayed coordinates are in MNI space. Brain areas and dynamic states were extracted from previous work (Vergara et al, 2018). Each row uses data from a different subject where the corresponding pattern was observed.…”
Section: Real Data Examplementioning
confidence: 99%